2007
DOI: 10.1002/sce.20253
|View full text |Cite
|
Sign up to set email alerts
|

From peripheral to central, the story of Melanie's metamorphosis in an urban middle school science class

Abstract: Identity formation is a critical dimension of how and why students engage in science to varying degrees. In this paper, we use the lens of identity formation, and in particular identities in practice, to make sense of how and why Melanie, over the course of sixth grade, transformed from a marginalized member of the science class with a failing grade to a highly valued member of the sixth-grade science community with a perfect score of a 100% for the sixth-grade exit project. Our findings reveal that the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 29 publications
0
61
0
Order By: Relevance
“…They discuss animal and plant care with Mr. M, work with him to keep the animals clean, and accompany him to the pet store across the street to get supplies. We found that gaining expertise in these informal spaces and building a relationship with Mr. M often translated into students being better positioned to participate more centrally in the formal science lessons (see Tan & Calabrese Barton, 2008). Table 1 summarizes the pedagogical strategies Mr. M enacts to tap into the nontraditional resources in creating these figured worlds.…”
Section: Science Class As a Figured World For Diverse Authentic Scimentioning
confidence: 95%
“…They discuss animal and plant care with Mr. M, work with him to keep the animals clean, and accompany him to the pet store across the street to get supplies. We found that gaining expertise in these informal spaces and building a relationship with Mr. M often translated into students being better positioned to participate more centrally in the formal science lessons (see Tan & Calabrese Barton, 2008). Table 1 summarizes the pedagogical strategies Mr. M enacts to tap into the nontraditional resources in creating these figured worlds.…”
Section: Science Class As a Figured World For Diverse Authentic Scimentioning
confidence: 95%
“…In multiple projects with racially diverse children from low-income backgrounds, Barton and colleagues (Barton 2003;Basu and Barton 2007;Tan and Barton 2008) have found that situating science learning in contexts and problems relevant to the participants, and positioning participants as central creators of knowledge that could be used to solve problems encouraged participants to engage with science and see themselves as scientists. Rather than focusing on teaching specific science content, this approach connected to the science in participants' daily lives to reconceptualize science as a context in which the participants were already experts (Barton 2003).…”
Section: Fostering Positive Attitudes Toward Science For All Participmentioning
confidence: 96%
“…But, they are also performances we enact as we interact with others [Gee, 2002;Holland, Lachicotte, Skinner, & Cain, 1998] -identities-in-practice , carved out in 'figured worlds' peopled by figures, characters, and actors who carry out tasks with distinguishable perspectives, styles, and orientations. As people become more (or less) central members of a community (i.e., a classroom community), changes in identity accompany changes in position and status [Berry, 2008;Carlone & Johnson, 2007;Jackson, 2009;Tan & Barton, 2008;Varelas, Becker, Luster, & Wenzel, 2002]. Changes in position and status, in turn, offer people different opportunities to engage with ideas, constructs, processes, and artifacts that are available in the community in narrated and performed ways.…”
Section: Clic: a Pedagogical And Research Frameworkmentioning
confidence: 99%